PENGUASAAN KOSAKATA ANAK TUNARUNGU DALAM PEMBELAJARAN MEMBACA MELALUI PENERAPAN METODE MATERNAL - Hermanto Hermanto (MAJALAH ILMIAH PEMBELAJARAN, 2011)
Mastery of vocabulary is one of the fundamental skills that arecritical to the implementation of the communication process.Communication is both verbal communication or writtencommunication or reading. Persons with hearing impairment to thecondition causing the loss of auditory function process controlupgrades vocabulary can not evolve naturally and result in limitedcommunication capabilities. For that, the increase in vocabularymastery for them must continue to be made and pursued in particular.One effort that can be done to improve the mastery of the vocabularyof children with hearing impairment through reading instructional withmaternal reflective approach. There are two steps in readinginstructional with maternal reflective method, that is ideo-visualreading, and receptive reading. But reading the receptive itself isdivided into two phases, namely reading stage receptive vocabulary,and reading the receptive stage of the structure. Thus to improve themastery of the vocabulary of children with hearing impairmentthrough the maternal method, the ideo-visual literacy, and readingshould be instilled early receptive. This instructional must beimplemented correctly, systemic-systematic, programmed, andsustainable of all the teachers.